2012
DOI: 10.1007/s00246-012-0505-3
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Treated Prevalence of Congenital Heart Disease in a Pediatric Cohort

Abstract: Extant epidemiologic results for pediatric congenital heart disease (CHD) are dated. Given the degree of variability in previous prevalence estimates and the rapid changes in pediatric cardiology diagnostic and treatment procedures, a reexamination of these rates represents a potentially important update in this area of inquiry. This report characterizes the prevalence rates of children with CHD in one state's treated pediatric population by type of lesion and in comparison with published rates from previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 14 publications
1
19
1
Order By: Relevance
“…19 Using “recalled” diagnoses of congenital heart defects from the NHIS combined with other national databases (US Census, National Vital Statistics System, Human Mortality Database), the birth prevalence is 3.3 and 3.2 per 1000 for males and females, respectively. 20 Incidence (birth prevalence) in Europe is reported as 6.9 per 1000 births; birth prevalence in Asia is reported as 9.3 per 1000.…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…19 Using “recalled” diagnoses of congenital heart defects from the NHIS combined with other national databases (US Census, National Vital Statistics System, Human Mortality Database), the birth prevalence is 3.3 and 3.2 per 1000 for males and females, respectively. 20 Incidence (birth prevalence) in Europe is reported as 6.9 per 1000 births; birth prevalence in Asia is reported as 9.3 per 1000.…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…Atrial septal defects (ASDs) are a relatively common anomaly, representing 6-8% of all congenital heart disease (CHD) cases [1]. Most ASDs were traditionally diagnosed based on symptoms such as heart murmur, cardiomegaly and chest pain [2]; however, in modern practice, echocardiography is frequently used as a tool in neonatal units to evaluate respiratory problems or cardiomegaly and to examine benign murmurs in otherwise healthy babies.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Our study demonstrated the incidence of clinically significant CHD, defined as requiring intervention or long term cardiology follow-up, to be 1%. [2][3][4][5] Our study demonstrated the incidence of clinically significant CHD, defined as requiring intervention or long term cardiology follow-up, to be 1%.…”
Section: Discussionmentioning
confidence: 62%